Church-State Relations in the 1899 Malolos Constitution: Filipinization and Visions of National Community - Aguilar, Filomeno V, Jr (Archīum Ateneo, 2015)
The most contentious issue in the Revolutionary Congress that crafted the 1899 Malolos Constitution pertained to the separation of church and state, which won by a mere one vote. Until now this episode in Philippine history has not received a satisfactory explanation, which this article seeks to offer. The debate in Malolos, as argued here, was profoundly divisive because the two sides were driven by differing visions of national community. A crucial point was the Filipinization of the Catholic Church, which the proponents of church-state unity championed and which their opponents sidestepped. Even as the debate raged, however, Aguinaldo's revolutionary government acted on the church-state issue out of political expediency. In the end, the issue that Filipino elites could not resolve was settled by US colonialism, which imposed church-state separation without Filipinization.